2014
DOI: 10.3109/00016357.2014.936036
|View full text |Cite
|
Sign up to set email alerts
|

Dental care access among individuals with Down syndrome: a Malaysian scenario

Abstract: A high proportion of parents appear to be able to access dental and medical care for their DS child. However, some parents perceived difficulty in finding oral healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Four studies measured coverage of dental services, all of which focussed on children with intellectual disabilities Khatib et al and Al Habeshneh et al found lower previous dental attendance for children with intellectual disability in Egypt, and Jordan respectively [ 37 , 38 , 39 ]. Oredugba et al and Rahim et al found no difference in any dental treatment received amongst children with intellectual disability in Nigeria and Malaysia respectively [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies measured coverage of dental services, all of which focussed on children with intellectual disabilities Khatib et al and Al Habeshneh et al found lower previous dental attendance for children with intellectual disability in Egypt, and Jordan respectively [ 37 , 38 , 39 ]. Oredugba et al and Rahim et al found no difference in any dental treatment received amongst children with intellectual disability in Nigeria and Malaysia respectively [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles were evenly distributed between qualitative and quantitative study designs. Fourteen studies were qualitative [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], eleven were quantitative [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and five were mixed methods [ 20 , 47 , 48 , 49 , 50 ]. Investigators in six studies completed secondary analyses, four using data from the National Survey of Children with Special Health Care Needs (NS-CSHCN) [ 51 , 52 , 53 , 54 ], one completing a chart review [ 7 ], and one using the Intellectual Disability Exploring Answers (IDEA) database [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each of these measures was used in two studies included in the review [ 20 , 36 , 38 , 48 , 56 , 57 ]. Additionally, two studies used the Oral assessment in DS Questionnaire [ 37 , 44 ]. The Emotionality, Activity, Sociability Survey, Family Adaptability and Cohesion Evaluation Scale, the brief Family Assessment Measure (FAM), Family Support Scale (FSS), Family Coping Index (FCI), Family Environment Scale, Family Index of Regeneratively and Adaptation (FIRA-G), Parent-caregiver Perception Questionnaire (P-CPQ), Perceived Social Support Scale (PSSS), Family Assessment Device (FAD), Beck Depression Inventory (BDI), Index of Social Competence (ISC) and Family APGAR were each used in one study [ 36 , 38 , 40 , 43 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although DS individuals’ families may encounter more challenges in daily life, their OHRQoL was not different from families of individuals without DS. The results suggest that the impact of oral conditions may be considered less relevant by the family members of individuals with DS compared with all the daily care that this population needs …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dental caries and the clinical consequences of untreated dental caries can cause pain and functional limitations during chewing and speech, which results in changes in the daily life of the children/adolescents and their families . Parents/caregivers of children/adolescents with DS also encounter additional issues with respect to dental access for their children, given the small number of practitioners well trained to provide dental services to this population, resulting in frequent unfavorable dental treatment experiences for the children/adolescents and for their guardians …”
Section: Discussionmentioning
confidence: 99%